Effort of NGO in Promoting Comprehensive Sexuality Education to Improve Quality of Life among Local and Refugee Communities - Yeo Kee Jiar; Shih Hui Lee; Lina Handayani (Institute of Advanced Engineering and Science, 2018)
Federation of Reproductive Health Association, Malaysia (FRHAM) is a pioneer Non-governmental Organization (NGO) in disseminating the knowledge and services of sexual reproductive health in Malaysia. A qualitative case study research design was employed to explore the roles of FRHAM in promoting Comprehensive Sexuality Education (CSE) for the well-being of locals and refugees’ communities. In-depth interviews were conducted with the staffs of FRHAM to inquire about their effort in delivering their services. The interviews were recorded, transcribed, coded and emergent themes were identified. FRHAM had played a part as educator, service provider, advocate and actively involved in improving the quality of life among the refugee community. The organization had developed modules for CSE and conducted programs for dissemination of knowledge. They also collaborated with local governmental agencies and other NGOs to promote awareness and utilization of services among the communities. Nevertheless, promoting CSE had experienced many challenges in Malaysia. The perceptions of Malaysian viewing sexuality education as taboos, cultural factors, the reluctance of educators in delivering, and the low visibility of FRHAM are the barriers encountered by FRHAM in promoting CSE. FRHAM recommended including parents, teachers and other stakeholders in the promotion of CSE and acknowledging CSE as an official subject to be implemented in schools. The information from this study may encourage more partnerships between the stakeholders, policy makers and NGOs for providing high quality CSE and sexual reproductive health services.